Confucianisms for a Changing World Cultural Order - Ames, Roger T.; Hershock, Peter D. (Confucian Cultures, 2017)
The rise of Asia has precipitated a dramatic sea change in the world's economic and political orders, and deepening global predicaments, including climate change, migration, and increasing inequalities of wealth and opportunity, pose new challenges. This book critically explores how the pan-Asian phenomenon of Confucianism offers alternative values and depths of ethical commitment that cross national and cultural boundaries to provide a new response to these challenges. Examining the meaning and value of Confucianism in the twenty-first century, the contributors-leading scholars from universities around the world-wrestle with several key questions: What are Confucian values within the context of the disparate cultures of China, Japan, Korea, and Vietnam? What are the limits and historical failings of Confucianism and how are these to be critically addressed? How must Confucian culture be reformed if it is to become relevant as an international resource for positive change?